2015
DOI: 10.1021/am507636k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Environmental Stability Induced by Effective Polarization of a Polar Dielectric Layer in a Trilayer Dielectric System of Organic Field-Effect Transistors: A Quantitative Study

Abstract: We report a concept fabrication method that helps to improve the performance and stability of copper phthalocyanine (CuPc) based organic field-effect transistors (OFETs) in ambient. The devices were fabricated using a trilayer dielectric system that contains a bilayer polymer dielectrics consisting of a hydrophobic thin layer of poly(methyl methacrylate) (PMMA) on poly(vinyl alcohol) (PVA) or poly(4-vinylphenol) (PVP) or polystyrene (PS) with Al2O3 as a third layer. We have explored the peculiarities in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…As shown in Figure d, the device exhibits a saturated mobility of 1.38 cm 2 V −1 s −1 at a very low threshold voltage of −1.9 V. Besides, it also shows a small hysteresis with a high on/off ratio of 1.2 × 10 5 . The increasing carrier mobility could be attributed to the enhanced polarization of hydroxyl groups in the presence of water molecules at the C8‐BTBT/CYTOP interface . The device shows a maximum brightness of 13 400 cd m −2 at V g = −24 V and V d = −24 V (Figure b), which is higher than device B1.…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure d, the device exhibits a saturated mobility of 1.38 cm 2 V −1 s −1 at a very low threshold voltage of −1.9 V. Besides, it also shows a small hysteresis with a high on/off ratio of 1.2 × 10 5 . The increasing carrier mobility could be attributed to the enhanced polarization of hydroxyl groups in the presence of water molecules at the C8‐BTBT/CYTOP interface . The device shows a maximum brightness of 13 400 cd m −2 at V g = −24 V and V d = −24 V (Figure b), which is higher than device B1.…”
Section: Resultsmentioning
confidence: 96%
“…Inorganic/organic bilayer and inorganic multilayer structures could suppress the through-plane leakage current by termination of the defects, grain boundaries, and clusters in the films [14,30,31]. It was reported that polymer/polymer bilayer structures could reduce the leakage current by tuning the surface morphology and termination of the pinholes [32][33][34]. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Since PVA and PVP are polar polymers with abundant hydroxyl groups attached to polymer chains, the polarizations of hydroxyl dipoles would be sensitive to the magnitude and direction of the electrical field (bias) [27]. The influence of applied gate bias on the orientation of hydroxyl groups in the PVA layer was studied by Tsai et al [20].…”
Section: Resultsmentioning
confidence: 99%
“…The performance and stability of OFETs were improved [27], but the third layer Al 2 O 3 was grown by converting a portion of Al film by an anodization process, even the annealing temperature of the solution process Al 2 O 3 was at least 150 °C [28], which was not compatible with plastic substrates [29]. In this work, we demonstrate a trilayer dielectric system consisting of a polar dielectric layer inserted between hydrophobic polymer layers, which is fabricated with a solution process.…”
Section: Introductionmentioning
confidence: 99%